Resistance wheel running improves contractile strength, but not metabolic capacity, in a murine model of volumetric muscle loss injury - Schifino, Albino G.; Raymond‐Pope, Christiana J.; Heo, Junwon; McFaline‐Figueroa, Jennifer; Call, Jarrod A.; Greising, Sarah M. (Experimental physiology, 2023)
The primary objective of this study was to determine if low‐ or high‐resistance voluntary wheel running leads to functional improvements in muscle strength (i.e., isometric and isokinetic torque) and metabolic function (i.e., permeabilized fibre bundle mitochondrial respiration) after a volumetric muscle loss (VML) injury. C57BL/6J mice were randomized into one of four experimental groups at age 12 weeks: uninjured control, VML untreated (VML), low‐resistance wheel running (VML‐LR) and high‐resistance wheel running (VML‐HR). All mice, excluding the uninjured, were subject to a unilateral VML injury to the plantar flexor muscles and wheel running began 3 days post‐VML. At 8 weeks post‐VML, peak isometric torque was greater in uninjured compared to all VML‐injured groups, but both VML‐LR and VML‐HR had greater (∼32%) peak isometric torque compared to VML. All VML‐injured groups had less isokinetic torque compared to uninjured, and there was no statistical difference among VML, VML‐LR and VML‐HR. No differences in cumulative running distance were observed between VML‐LR and VML‐HR groups. Because adaptations in VML‐HR peak isometric torque were attributed to greater gastrocnemius muscle mass, atrophy‐ and hypertrophy‐related protein content and post‐translational modifications were explored via immunoblot; however, results were inconclusive. Permeabilized fibre bundle mitochondrial oxygen consumption was 22% greater in uninjured compared to VML, but there was no statistical difference among VML, VML‐LR and VML‐HR. Furthermore, neither wheel running group demonstrated a change in the relative protein content of the mitochondrial biogenesis transcription factor, peroxisome proliferator‐activated receptor γ coactivator 1‐α (PGC‐1α). These results indicate that resistance wheel running alone only has modest benefits in the VML‐injured muscle. What is the central question of the study? Does initiation of a resistance wheel running regimen following volumetric muscle loss (VML) improve the functional capacity of skeletal muscle? What is the main finding and its importance? Resistance wheel running led to greater muscle mass and strength in mice with a VML injury but did not result in a full recovery. Neither low‐ nor high‐resistance wheel running was associated with a change in permeabilized muscle fibre respiration despite runners having greater whole‐body treadmill endurance capacity, suggesting resilience to metabolic adaptations in VML‐injured muscle. Resistance wheel running may be a suitable adjuvant rehabilitation strategy, but alone does not fully mitigate VML pathology.